Optimal fuzzy logic-based adaptive controller equipped with DFIG wind turbine for frequency control in stand alone power system - Sa-Ngawong, Nattapol; Ngamroo, Issarachai (My University, 2013)
This paper deals with an adaptive controller design by an optimal fuzzy logic of doubly fed induction generator (DFIG) wind turbine for frequency control in the stand alone power system. Since the DFIG wind turbine has the ability of active power control, this makes the possibility of system frequency control contribution by DFIG. The optimal fuzzy logic adapts the control parameters of the supplement controller equipped with the DFIG wind turbine so that the active power output can be controlled to alleviate the frequency deviation due to load changes. In the fuzzy logic design, the membership function and the control rules are automatically optimized by the particle swarm optimization. Simulation study confirms that the control effect and robustness of the proposed adaptive controller is superior to that of the conventional controller with fixed parameters against various random load changes and system parameters variation. © 2013 IEEE.
Keywords: Doubly fed induction generator wind turbine; frequency control; fuzzy control; particle swarm optimization